Effect of Physical Exercise on Depression in Patients at Surakarta Mental Hospital - Nurcahyo, Firmanto Adi; Kusumowardani, Andreany; Untari, Rita; Nugroho, Pebriyanto Nindyo (ANIMA Indonesian Psychological Journal, 2013)
The high prevalence of depressive mental disorder along with its serious impacts requires a comprehensive treatment with pharmacological and non-pharmacological approaches. Phy- sical exercise as a method of non-pharmacological therapy has been shown to be beneficial for the prevention and the cure of diseases. The purpose of this study was to determine the effect of physical exercise on the level of depression in patients with mild and moderate depression in Surakarta Mental Hospital. This study was an experimental study. The results showed that overall exercise had a significant influence on the decrease in the level of depression (t = 7.375, p = .002). However, physical exercise did not have a significant effect on reducing depression levels in the group of mild depression (t = 1.858, p = .529). Several limitations of this study may lead to the results of this study were not entirely as hypothesized. Prevalensi gangguan jiwa depresi yang tinggi serta disertai dampak yang serius memerlukan penanganan komprehensif secara farmakologis maupun non farmakologis. Latihan fisik sebagai salah satu metode terapi non farmakologis, terbukti telah memberikan manfaat yang besar bagi pencegahan dan penyembuhan penyakit. Tujuan penelitian ini adalah menguji pengaruh latihan fisik terhadap tingkat depresi pada pasien dengan tingkat depresi ringan dan sedang di Rumah Sakit Jiwa Daerah Surakarta. Jenis penelitian ini adalah eksperimen. Hasil penelitian menunjukkan bahwa secara keseluruhan latihan fisik memberikan pengaruh yang signifikan pada penurunan tingkat depresi (t = 7.375, p = .002). Namun demikian, latihan fisik tidak memberikan pengaruh yang signifikan bagi penurunan tingkat depresi pada kelompok depresi ringan (t = 1858, p = .529). Beberapa keterbatasan dalam penelitian ditengarai mempengaruhi hasil dalam penelitian ini sehingga tidak sesuai dengan hipotesis yang diajukan.